2019
DOI: 10.18805/ijare.a-5319
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Allelopathic Effect of Aqueous Leaf Extract of Putranjiva Roxburghii Wall. on Seed Germination and Early Growth of Chickpea (Cicer Arietinum L.)

Abstract: The present study reveals the allelopathic effect of aqueous leaf extracts of Putranjiva roxburghii Wall. on seed germination and early growth stages of an economically important plant chickpea (Cicer arietinum L.). Aqueous leaf extracts at 0, 5, 10, 15, 25, 35, 50, 75 and 100% concentrations were applied to determine their effect on seed germination and early growth stages under laboratory conditions. Laboratory-based experiments with three replicates were used to arrange treatments accordingly. After 5 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Sahoo et al (2007) suggested that aqueous leaf extracts of two tree species showed a reduction of the fresh and dry weight of maize. Similar results were also reported by Oraon and Mondal (2020) that aqueous leaf extracts of Putranjiva roxburghii showed that dry weight of chickpea seeds significantly decreased upon increasing concentrations.…”
Section: Biomass Production Of Root and Shootssupporting
confidence: 90%
“…Sahoo et al (2007) suggested that aqueous leaf extracts of two tree species showed a reduction of the fresh and dry weight of maize. Similar results were also reported by Oraon and Mondal (2020) that aqueous leaf extracts of Putranjiva roxburghii showed that dry weight of chickpea seeds significantly decreased upon increasing concentrations.…”
Section: Biomass Production Of Root and Shootssupporting
confidence: 90%
“…e present findings are in accordance with Das et al (2012), who found that the aqueous leachates of leaf litter of seven tree species significantly (p < 0.01) reduced the SVI of gram (chickpea) seeds. Alqarawi et al (2018) reported a strong inhibitory effect of aqueous leaf extracts of Rhazya stricta on SVI of Salsola villosa, while Oraon and Mondal (2020) reported that the SVI of chickpea decreased significantly (p < 0.001) with increased concentrations of aqueous leaf extracts of Putranjiva roxburghii.…”
Section: Discussionmentioning
confidence: 99%
“…P. caninum leaf extract can suppress the pathogenic curvularia, although the pathogenic curvularia also has phytotoxic substances against other organisms such as inhibition of bacteria such as Escherichia coli and also has antioxidant activity and inhibition of acetylcholinesterase (Kaaniche et al, 2019). This is also supported by research by Oraon and Mondal (2020) that the initial growth of Cicer Arietinum L. was hampered after being given a Putranjiva roxburghii Wall leaf extract license. at high concentrations (100%), because the extract contains allelopathic substances.…”
Section: Intensity Of Curvularia Diseasementioning
confidence: 86%